2015
DOI: 10.1371/journal.pone.0141314
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of AbeD, an RND-Type Membrane Transporter in Antimicrobial Resistance in Acinetobacter baumannii

Abstract: Background Acinetobacter baumannii is becoming an increasing menace in health care settings especially in the intensive care units due to its ability to withstand adverse environmental conditions and exhibit innate resistance to different classes of antibiotics. Here we describe the biological contributions of abeD, a novel membrane transporter in bacterial stress response and antimicrobial resistance in A. baumannii.ResultsThe abeD mutant displayed ~ 3.37 fold decreased survival and >5-fold reduced growth in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 36 publications
(59 reference statements)
1
32
0
Order By: Relevance
“…Identification of AoSoxR Target Genes-To identify SoxRregulated genes, we used the A. oleivorans genome and transcriptome data indicating possible SoxR binding sites (24,(31)(32)(33). Although five possible candidate promoters (AOLE_ 16635 encoding a putative L-PSP endoribonucleases, AOLE_ 18450 encoding a membrane protein, argT, scpA, and hisZ) were found using a putative SoxR binding site, two of them (scpA and hisZ) were not induced by RACs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Identification of AoSoxR Target Genes-To identify SoxRregulated genes, we used the A. oleivorans genome and transcriptome data indicating possible SoxR binding sites (24,(31)(32)(33). Although five possible candidate promoters (AOLE_ 16635 encoding a putative L-PSP endoribonucleases, AOLE_ 18450 encoding a membrane protein, argT, scpA, and hisZ) were found using a putative SoxR binding site, two of them (scpA and hisZ) were not induced by RACs.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, AOLE_16640 (co-transcribed with sinE) and AOLE_05515 were directly regulated by activated SoxR. It was recently reported that the abuO gene encoding a TolC-like outer membrane protein and the abeD gene encoding a RNDtype membrane transporter of A. baumannii AYE were directly regulated by SoxR (31,32). A putative outer membrane protein (AOLE_18125) that showed 94% amino acid identity with AbuO was up-regulated 4.1-fold with PMS treatment; however, there was no difference in the presence of PQ in our transcriptome analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations